2001
DOI: 10.1086/501945
|View full text |Cite
|
Sign up to set email alerts
|

Improved Compliance With Universal Precautions in the Operating Room Following an Educational Intervention

Abstract: Observation of surgical personnel in four specialties (cardio-thoracic, general, gynecologic, and orthopedic) in the operating room was performed prior to implementation of an educational intervention designed to improve compliance with Universal Precautions and at 1- and 2-years post-intervention. Use of protective eyewear and double gloving increased following the intervention, whereas the incidence of documented blood and body fluid exposures decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…2003), whilst a few were carried out over a period of one year or more (Jeffe et al. 1999, Kim et al. 2001, Pratt et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2003), whilst a few were carried out over a period of one year or more (Jeffe et al. 1999, Kim et al. 2001, Pratt et al.…”
Section: Discussionmentioning
confidence: 99%
“…No UK studies were identified, and only one study that measured the effect of an intervention over an extended period of time i.e. years, Kim et al. (2001), the results of which showed no significant results.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to infectious material can be minimized if they adhere to standard precautions (SPs). [7] Besides the documented role of hand washing and SPs, other non-pharmacological interventions such as cleaner hospital environment have been shown to significantly reduce the rate of HCAI. [8] But these are often overlooked in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study conducted in USA revealed that well-trained hospital staff plays an important role in health care performances [16][17]. And also a study conducted in China found that dramatic improvement was observed after the training program regarding participants' attitude and practice on infection Prevention [18].…”
Section: Discussionmentioning
confidence: 99%